BENTUK AMR DAN NAHI DALAM SURAT AL-HUJURAT - Miftakhurifka An-Nisa; Aulia Subita; Meidias Abror Wicaksono (Prosiding Konferensi Nasional Bahasa Arab, 2021)
Abstract:This study aims to analyze the forms of amr and nahi contained in Surat al-Hujurat. The method used in this study titled